The Effectiveness Of Criminal Law Enforcement Against Juvenile Crime In The Murder Case Of A Junior High School Student At The Chinese Cemetery In Palembang - Ria Fadillah (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
In Indonesia, managing juvenile criminal cases is a priority. To safeguard the rights of law-breaking children, Indonesia passed Law No. 11 of 2012 on the Juvenile Criminal Justice System. This study applies a normative juridical technique to examine relevant legislation, such as statutes and regulations. To better prosecute significant juvenile offenders, Article 96 of the Juvenile Criminal Justice System Law (UU SPPA) must be strengthened. This article mandates that law enforcement officials undergo specialized training in child psychology. Punishment for murder should not be based on the identity of the subject or suspect, but rather emphasize the motive and the crime committed by the suspect. This approach ensures that the punishment handed down is proportionate to the crime committed by the individual or group.